Synergistic effects of kaolin clay on intumescent fire retardant coating composition for fire protection of structural steel substrate - Ullah, S. (Elsevier Ltd, 2014)
Intumescent coating is an insulating material designed to decrease heat transfer to a substrate structure. This research presents the results of different formulations developed to study the effects of kaolin clay on expansion of coating and heat shielding during the fire test. The intumescent coating formulations (ICFs) were tested at 950Â°C for 1 h. The results showed that the coatings were stable and well bound with substrate. The coatings were characterized by using Field emission scanning electron microscopy (FESEM), X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), Thermogravimetric analysis (TGA) and X-ray photoelectron spectroscopy (XPS). The morphology of char was studied by FESEM on the coating after fire test. XRD and FTIR showed the presence of carbon (graphite), boron phosphate, boron oxide, sassolite and kaolinite in the residual char. TGA showed that kaolin clay reinforced formulation; IF5-KC enhanced 49 residual weight than that of IF-Control formulation. XPS analysis showed that elemental composition of IF5-KC char residue gave 41.80 carbon content in the residual char. An accelerated weathering test ASTM D 6695-03 showed that IF5-KC coating sustained its integrity up to 90 days under accelerated weathering chamber. Â© 2014 Elsevier Ltd. All rights reserved.